QUALITY MANAGEMENT OF ISLAMIC EDUCATION FROM THE PERSPECTIVE OF THE QUR’AN AND HADITH: Manajemen Mutu Pendidikan Islam dalam Perspektif Al Qur’an Dan Hadits - Indria Ningsih; Bedjo Sujanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
The world of education continues to face challenges, including constantly changing curricula, low teacher quality, stagnant teacher welfare, low student competency, and many others. The general causes of the low quality of education in Indonesia include issues of effectiveness, efficiency, and standardization of teaching. Public interest in quality Islamic educational institutions is growing. Reality shows that quality educational institutions are increasingly sought after by the public, even though access to them requires higher costs. The growth of quality Islamic schools is increasing, such as Integrated Islamic Schools, Islamic Boarding Schools, and Islamic Nature Schools. This growth presents an opportunity for Islamic education to grow and attract more public attention, naturally by improving the quality of education and institutions. The increasing public interest in sending their children to Islamic schools or Islamic educational institutions is undoubtedly due to the quality of the schools. Islamic schools or educational institutions must be able to build and maintain quality within their management systems. Improving the quality of educational institutions also needs to be driven by Islamic thought, grounded in the Qur'an and Hadith. Quality management is a crucial aspect in improving the quality of Islamic educational management by implementing Total Quality Management (TQM). Through an in-depth study, the author aims to demonstrate how the Qur'an and Hadith view quality management, or the quality management of Islamic education, within an Islamic educational institution. This study explores how good quality management aligns with the Qur'an and Hadith. Quality management is expected to improve the quality of managerial practices and build a more relevant, adaptive, and meaningful education system for society.